2022
DOI: 10.1590/1984-3143-ar2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of extracellular matrix related proteins in normal and cryptorchid ziwuling black goat testes

Abstract: The Ziwuling black goat is an indigenously in China, their offspring are frequently affected by congenital cryptorchidism. The extracellular matrix (ECM) contains cytokines and growth factors that regulate the development of the testis, and component changes often result in pathological changes. Cryptorchidism is closely related to structural changes in ECM. In this study, the histochemical staining, immunohistochemical, immunofluorescence and Western blot combined with semi-quantitative analysis was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This observation may indicate changes in the ECM during transinguinal descent via hyaluronic acid metabolism. Recently, Wang et al [ 59 ] compared the ECM components in normal and cryptorchid ziwuling black goat testes and found that the distribution of major ECM components affected the development of seminiferous tubules and Leydig cells. We then constructed the miRNA-lncRNA-mRNA, miRNA-circRNA-mRNA, and miRNA-circRNA-lncRNA-mRNA interaction networks for genes related to the first testicular descent.…”
Section: Discussionmentioning
confidence: 99%
“…This observation may indicate changes in the ECM during transinguinal descent via hyaluronic acid metabolism. Recently, Wang et al [ 59 ] compared the ECM components in normal and cryptorchid ziwuling black goat testes and found that the distribution of major ECM components affected the development of seminiferous tubules and Leydig cells. We then constructed the miRNA-lncRNA-mRNA, miRNA-circRNA-mRNA, and miRNA-circRNA-lncRNA-mRNA interaction networks for genes related to the first testicular descent.…”
Section: Discussionmentioning
confidence: 99%